Structural Basis of Bone Fragility in Young Subjects with Inflammatory Bowel Disease: A High-resolution pQCT Study of the SWISS IBD Cohort (SIBDC). Issue 8 (29th May 2017) - Pepe, Jessica; Zawadynski, Sophie; Herrmann, Francois R.; Juillerat, Pascal; Michetti, Pierre; Ferrari-Lacraz, Sylvie; Belli, Dominique; Ratib, Osman; Rizzoli, René; Chevalley, Thierry; Ferrari, Serge L.
Abstract : Background: The onset of inflammatory bowel disease (IBD) during childhood/adolescence compromises peak bone mass acquisition and predisposes to fractures later in life. However, the structural basis for bone fragility in young adults with IBD remains unknown. Methods: One hundred two young subjects from the Swiss IBD cohort were included. Areal bone mineral density (aBMD) at distal radius, hip, and spine as well as morphometric vertebral fractures were assessed using dual-energy x-ray absorptiometry technique. Volumetric (v)BMD, trabecular, and cortical bone microstructure at the distal radius and tibia were assessed by high-resolution peripheral quantitative computed tomography. Areal, vBMD, and microstructure were compared between patients with IBD and healthy matched controls (n = 389). Multiple regression analysis was used to evaluate variables associated with bone microarchitecture and fractures. Results: Clinical fractures were reported in 37 IBD subjects (mean age 23 yrs), mostly of the forearm; 5 subjects had morphometric vertebral fractures. After adjusting for age, sex, and height, tibia trabecular (Tb)vBMD, thickness, and distribution were significantly associated with fractures, whereas aBMD was not. After adjusting for aBMD, radius Tb distribution and tibia (Tb)vBMD and trabecular thickness still remained associated with fractures. Compared with healthy controls, patients with IBD had significantly lower aBMD at all sites, as well as alteration in (Tb)vBMD and trabecular microstructure at the distal radius and tibia, and these alterations were correlated with disease severity. Conclusions: Young patients with IBD have low aBMD and altered trabecular bone microarchitecture compared with healthy controls. The latter is independently associated with fractures and may predispose increased susceptibility to fragility fractures throughout life.